Water Source Preferences and Water Quality Perceptions Among Women in the Eastern Region, Ghana - Chew, Jhanel. (2017)
Abstract: Previous research in the Eastern Region of Ghana has shown that residents who have access to improved water sources, such as boreholes and covered wells, will still choose to collect water from unimproved sources, such as rivers and uncovered wells. To assess why this occurs, two field study visits were conducted to coincide with Ghana's rainy and dry seasons. In the first study, semi-structured in-depth interviews were conducted among a convenience sample of 26 adult female subjects in four rural communities. Each subject was asked about their attitudes and perceptions of water sources in their community. The second field study involved field observations of four women for up to four days in length to provide context for water collection and use of water from different sources in homes. A grounded theory approach was used to identify three themes that informed water source choices. The themes were water quality perception, collection of and access to water, and the dynamic interaction of these. Based on the field observations, a larger role for women in water management and supply decision-making would better advance the population health of their communities.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Civil Engineering.; Advisor: David Gute.; Committee: Fernando Ona, Sarah Pinto, Alexandra Kulinkina, and Laura Corlin.; Keywords: Behavioral sciences, Social research, and Public health.